Radiation Damage of LaMgAl11O19 and CeMgAl11O19 Magnetoplumbite. Issue 10 (9th August 2013) - Men, Danju; Patel, Maulik K.; Usov, Igor O.; Pivin, J. C.; Porter, John R.; Mecartney, Martha L.; Mitchell, T.
<x xml:space="preserve">Abstract</x> Studies of radiation damage in magnetoplumbite‐type LaMgAl11O19 and CeMgAl11O19 are reported. Ion irradiation was conducted on ceramic composites containing a LaMgAl11O19 phase at 500°C with 10 MeV Au+ ions and on ceramic composites containing CeMgAl11O19 phase at 800°C with 92 MeV Xe+ ions. The radiation response of these similar LnMgAl11O19 (Ln = La and Ce) hexaaluminate magnetoplumbite phases was evaluated using transmission electron microscopy (TEM) and X‐ray diffraction (XRD). LaMgAl11O19 was amorphized by 10 MeV Au ions with swelling of the structure within an approximate 2 μm radiation depth from the irradiation surface. CeMgAl11O19 did not amorphize after 92 MeV Xe‐ion irradiation, but ion track damage contrast is seen in approximately 5 μm of the irradiated depth. SRIM Monte‐Carlo simulations of nuclear displacements correlate with the experimental results.